2018
DOI: 10.1002/bdm.2074
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Delay Discounting Within the Academic Domain

Abstract: It is important to better understand the decision-making processes involved in student procrastination, in order to develop interventions that reduce this common problem. Students may procrastinate because studying produces delayed reinforcers; however, no task measuring delay discounting of academic outcomes currently exists. In Experiment 1, we developed and piloted a measure of academic discounting modeled on titrating-amount tasks successfully used in the discounting literature. Participants made hypotheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…(2018) did not examine whether the size of the larger, delayed reward moderated the number of unsystematic discounting functions in their meta-analysis, but it is well demonstrated that reward value affects discounting rate (the magnitude effect, e.g., Olsen et al, 2018). Note, however, that if the undiscounted value of $200 is higher for workers located in India, the magnitude effect would predict shallower discounting for that group, whereas we observed steeper discounting.…”
Section: Exploratory Analysis Of Turk Worker Location and Master Worker Status And Rates Of Unsystematic Datamentioning
confidence: 63%
See 2 more Smart Citations
“…(2018) did not examine whether the size of the larger, delayed reward moderated the number of unsystematic discounting functions in their meta-analysis, but it is well demonstrated that reward value affects discounting rate (the magnitude effect, e.g., Olsen et al, 2018). Note, however, that if the undiscounted value of $200 is higher for workers located in India, the magnitude effect would predict shallower discounting for that group, whereas we observed steeper discounting.…”
Section: Exploratory Analysis Of Turk Worker Location and Master Worker Status And Rates Of Unsystematic Datamentioning
confidence: 63%
“…Yi et al (2017) found when participants completed the control-type condition before they completed the experimental condition, there was a significant difference in discounting rates between control and experimental conditions. However, when participants completed tasks in the reverse order, no significant differences were observed (see also Olsen et al, 2018, andYi, Pickover, Stuppy-Sullivan, Baker, &Landes, 2016, for similar patterns of effect). Therefore, we may also find that only participants who receive the "typical" decision context (i.e., YouWould) first will demonstrate subsequent differences in discounting rates.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Escaping from stressful and aversive situations might relieve stress and are thus rewarding. As an example, students are always faced with a trade-off when choosing between procrastinating or studying (Kirby et al, 2005;Olsen et al, 2018). One alternative is to complete the challenging academic tasks on time which leads to delayed rewards in the form of achieving academic and career goals (see e.g., Sutcliff et al, 2019).…”
Section: Psychological Flexibility and Academic Self-efficacy Beliefsmentioning
confidence: 99%
“…In contrast to the other atheoretical measures, AUC provides a measure of discounting which takes the value of all of the delays into account. The effects of experimental manipulations on delay discounting rate can differ depending on whether k or AUC is used (Olsen, Macaskill, & Hunt, 2018;Smith & Hantula, 2008). For example, Smith and Hantula (2008) found that k and AUC measures supported different conclusions about the combined effects of using different reinforcer magnitudes and discounting procedures.…”
Section: 𝑉 = a 1+𝑘dmentioning
confidence: 99%